Cyclin-Dependent Kinase-2 as a Target for Cancer Therapy: Progress in the Development of CDK2 Inhibitors as Anti-Cancer Agents - Chohan, Tahir A.; Qian, Haiyan; Pan, Youlu; Chen, Jian-Zhong (Current Medicinal Chemistry, 2015)
Cyclin-dependent kinase-2 (CDK2) is a member of protein kinase family. It plays an important role in regulating various events of eukaryotic cell division cycle. Accumulated evidences indicated that over expression of CDK2 should cause the abnormal regulation of cell-cycle, which would be directly associated with hyperproliferation in cancer cells. Therefore, CDK2 was regarded as a potentially therapeutic target for cancer therapy. Knowledge of crystallography and availability of X-ray crystal structure of CDK2 have enabled us to understand the mode of CDK2 inhibition, which facilitated the development of numerous CDK2 inhibitors. Some of the CDK2 inhibitors were investigated clinically for their potential as anti-cancer agents. In this review, we present the structure, functions and activation of CDK2 by cyclin binding with special focus on recent advances in the development of different classes of CDK2 inhibitors. We also summarize different strategies to achieve subtype specificity either by targeting a binding pocket other than ATP, i.e. allosteric ligand binding site or by natural protein inhibitors capable to disrupt CDK2-cyclin complexes. It is possible to develop pharmacologically relevant cytotoxic agents by specifically inhibiting CDK2 activity with lesser toxicity than traditional chemotherapeutic agents.
Keywords: CDK2